Theoretical investigation of high-efficiency organic electroluminescent material: HLCT state and hot exciton process. Issue 32 (3rd April 2017) - Pan, Yuyu; Huang, Jing; Li, Weijun; Gao, Yu; Wang, Zhiming; Yu, Dawei; Yang, Bing; Ma, Yuguang
Abstract : HLCT excited state with both high PL efficiency and a large fraction of singlet exciton generation in EL. We employed the DFT method to investigate twisting D–A molecules, and found that the twist angle had a significant effect on the CT component. Abstract : It has been proved that hybridized local and charge transfer (HLCT) excited state fluorescence emitters show great potential for next generation OLED materials with both high photoluminescence (PL) efficiency and a large fraction of singlet exciton generation in electroluminescence (EL). In order to reveal the relationship between molecular structure and photoelectric properties more deeply, we use density functional theory (DFT) and time-dependent density functional theory (TD-DFT) methods to calculate these novel functional materials. As examples, 4-(phenanthren-9-yl)- N, N -diphenylaniline (TPA-PA), 4-(anthracen-9-yl)- N, N -diphenylaniline (TPA-AN) and 4-(acridin-9-yl)- N, N -diphenylaniline (TPA-AC) are investigated in regards to geometries of ground-state and excited-state, HOMOs, LUMOs, as well as some excited-state character, absorption and emission spectra, and excited state energy surface scans. The results suggest that the twist angle of the D–A segment plays an important role in governing the CT components in the HLCT state of the studied complexes and based on the analysis of the excited state energy levels, a different electroluminescence mechanism was discussed.